2015
DOI: 10.1098/rspb.2015.0042
|View full text |Cite
|
Sign up to set email alerts
|

Infection of male rats withToxoplasma gondiiresults in enhanced delay aversion and neural changes in the nucleus accumbens core

Abstract: Rats infected with the protozoan parasite Toxoplasma gondii exhibit reduced avoidance of predator odours. This behavioural change is likely to increase transmission of the parasite from rats to cats. Here, we show that infection with T. gondii increases the propensity of the infected rats to make more impulsive choices, manifested as delay aversion in an intertemporal choice task. Concomitantly, T. gondii infection causes reduction in dopamine content and neuronal spine density of the nucleus accumbens core, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 51 publications
2
26
0
1
Order By: Relevance
“…Gaskell and Smith [43] have shown the genome of Toxoplasma contains two genes for tyrosine hydroxylase, the rate limiting enzyme of the dopamine synthesizing pathway. Indeed, an immunofluorescence study has demonstrated a high concentration of dopamine in Toxoplasma tissue cysts and their surroundings [44], but see also [45,46]. It is well known that increased levels of dopamine in certain brain structures is responsible for typical positive symptoms of schizophrenia, namely for hallucination and delusions [47].…”
Section: Association Of Toxoplasmosis With Mental Health Disordersmentioning
confidence: 97%
“…Gaskell and Smith [43] have shown the genome of Toxoplasma contains two genes for tyrosine hydroxylase, the rate limiting enzyme of the dopamine synthesizing pathway. Indeed, an immunofluorescence study has demonstrated a high concentration of dopamine in Toxoplasma tissue cysts and their surroundings [44], but see also [45,46]. It is well known that increased levels of dopamine in certain brain structures is responsible for typical positive symptoms of schizophrenia, namely for hallucination and delusions [47].…”
Section: Association Of Toxoplasmosis With Mental Health Disordersmentioning
confidence: 97%
“…Perturbations in catecholaminergic signalling with chronic infection have been observed, with elevated DA metabolites in the cortex and decreased NE in the cortex and amygdala and loss of amphetamine-induced locomotor activity (11,12). There are discrepancies in observations of changes in dopamine levels in the brain with T. gondii infection (13–17). Increased levels of dopamine in infected cells have been found when catecholaminergic cells are maintained at a physiological pH (8, 18–20).…”
Section: Introductionmentioning
confidence: 99%
“…One approach to testing the predictions of each of these three hypotheses involves manipulating the physiology of non-parasitized individuals with the aim of recreating the behaviour of the parasitized host (e.g. rodents, Tan et al, 2015;gammarids, PerrotMinnot et al, 2014). An experimental manipulation approach is appealing as it can potentially provide an insight into the nature of the connection between hosts and their parasites (HĂ©bert and AubinHorth, 2014).…”
Section: Introductionmentioning
confidence: 99%